2015
DOI: 10.1016/j.ijantimicag.2015.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Identification of synergists that potentiate the action of polymyxin B against Burkholderia cenocepacia

Abstract: Burkholderia cenocepacia and other members of the Burkholderia cepacia complex (Bcc) are highly multidrug-resistant bacteria that cause severe pulmonary infections in patients with cystic fibrosis. A screen of 2686 compounds derived from marine organisms identified molecules that could synergize with polymyxin B to inhibit growth of B. cenocepacia. At 1 µg/ml, five compounds synergized with polymyxin B and inhibited the growth of B. cenocepacia by more than 70% compared to growth in polymyxin B alone. Follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…In our assays, novobiocin had improved activity against B. cenocepacia at acidic pH. Loutet et al ( 44 ) showed synergy of novobiocin in combination with polymixin B and colistin against B. cenocepacia ( 44 ). Low MIC values for novobiocin have been reported against Burkholderia pseudomallei and Burkholderia mallei .…”
Section: Discussionsupporting
confidence: 53%
“…In our assays, novobiocin had improved activity against B. cenocepacia at acidic pH. Loutet et al ( 44 ) showed synergy of novobiocin in combination with polymixin B and colistin against B. cenocepacia ( 44 ). Low MIC values for novobiocin have been reported against Burkholderia pseudomallei and Burkholderia mallei .…”
Section: Discussionsupporting
confidence: 53%
“…Checkerboard assays were conducted with combinations of antibiotics (obtained from Sigma, St Louis, MO, USA) as previously described [ 10 ]. Initial assays against B. cenocepacia K56–2 were conducted in LB medium to select the most potent combination.…”
Section: Methodsmentioning
confidence: 99%
“…These include three β-lactams (ceftazidime, meropenem, and ticarcillin-clavulanate), the fluoroquinolone levofloxacin, and trimethoprim-sulfamethoxazole combo (co-trimoxazole) in addition to the bacteriostatic drugs minocycline and chloramphenicol. New therapeutic solutions are being explored [ 10 12 ], but until they can be translated into clinical use, Bcc-infected patients are in dire need of effective therapeutics. We aimed to bridge this gap by finding novel combinations of clinically available antibiotics that could eradicate Bcc bacteria at physiologically relevant concentrations and could be readily used in patients.…”
Section: Introductionmentioning
confidence: 99%
“…The susceptibility of the strains to Polymyxin B was further examined by diluting overnight cultures 1:100 in LB and adding 270 μl to each well in duplicate in a 96‐well plate. A series of Polymyxin B concentrations, prepared in distilled water with 0.2% (w/v) BSA and 0.02% (v/v) acetic acid were serially diluted 1:10 to give a final concentration in the range of 16 to 1024 μg/ml and the plate incubated in a Biotek Synergy H1 Microplate reader at 37°C with medium shaking and OD 600nm measured every 15 min for 20 h (Loutet et al, 2015 ). Assessment of mucoid phenotype Exopolysaccharide (EPS) production was assessed to determine the mucoid phenotype of the mutant strains of Bcc using Yeast extract mannitol (YEM) (2 g/L Yeast extract, 20 g/L d ‐mannitol, 15 g/L Agar no.2) plates (Lagatolla et al, 2002 ).…”
Section: Table A1mentioning
confidence: 99%
“…The susceptibility of the strains to Polymyxin B was further examined by diluting overnight cultures 1:100 in LB and adding 270 μl to each well in duplicate in a 96‐well plate. A series of Polymyxin B concentrations, prepared in distilled water with 0.2% (w/v) BSA and 0.02% (v/v) acetic acid were serially diluted 1:10 to give a final concentration in the range of 16 to 1024 μg/ml and the plate incubated in a Biotek Synergy H1 Microplate reader at 37°C with medium shaking and OD 600nm measured every 15 min for 20 h (Loutet et al, 2015 ).…”
Section: Table A1mentioning
confidence: 99%